High pressure treatments as an alternative to conventional thermal blanching - A case study on sweet green and red bell pepper fruits (Capsicum annuum L.) - Castro, S. (2012)
The effect of pressure treatments of 100 and 200MPa (10 and 20min) and thermal blanching at 70°C, 80°C and 98°C (1 and 2.5min), on green and red sweet bell peppers was compared. Pressure treated peppers showed a lower reduction on soluble protein and ascorbic acid contents (red peppers presented even an increased content of ascorbic acid of about 15-20%). Peroxidase (POD) and pectin methylesterase (PME) (whose activity was only quantifiable in green peppers) showed a higher stability to pressure treatments, particularly the latter enzyme, while polyphenol oxidase (PPO) was inactivated to the same final leve1 by the thermal blanching and pressure treatments. Pressure treatments resulted in similar (in green pepper) to slightly higher (in red pepper) microbial loads compared to blanching. Pressure treated presented similar to better f m e s s before and a f k tunnel freezing at -30°C, compared to thermally blanched peppers. Overall, pressure treated peppers present similar to better levels of the quality parameters studied, pointing to the possible use of pressure treatments as an alternative to the conventional thermal blanching of sweet bell peppers.